Potential of Salt Tolerant PGPR in Growth and Yield Augmentation of Wheat (Triticum aestivum L.) Under Saline Conditions - Nawaz, Aniqa; Shahbaz, Muhammad; Asadullah,; Imran, Asma; Marghoob, Muhammad U.; Imtiaz, Muhammad; Mubeen, Fathia (Frontiers in Microbiology, 2020)
Soil salinity has emerged as a major obstacle to meet world food demands. Halo-tolerant plant growth promoting rhizobacteria (PGPR) are potential bioinoculants to enhance crop productivity in saline agriculture. Current work was aimed at studying individual or synergetic impact of salt tolerant PGPR on wheat growth and yield under saline conditions. A pot experiment was conducted on two wheat genotypes (Aas-11; salt tolerant and Galaxy-13; salt sensitive) inoculated with Pseudomonas fluorescence, Bacillus pumilus, and Exiguobacterium aurantiacum alone and in consortium. The salt tolerant variety (Aas-11) exhibited maximum root fresh (665.2%) and dry biomass (865%), free proline (138.12%) and total soluble proteins (155.9%) contents, CAT (41.7%) activity and shoot potassium uptake (81.08%) upon inoculation with B. pumilus, while improved shoot dry weight (70.39%), water (23.49%) and osmotic (29.65%) potential, POD (60.51%) activity, enhanced root potassium (286.36%) and shoot calcium (400%) were manifested by E. aurantiacum. Highest shoot length (14.38%), fresh weight (72.73%), potassium (29.7%) and calcium (400%) acquisition as well as glycinebetaine (270.31%) content were found in plants treated with PGPR consortium. On the other hand, in the salt sensitive variety (Galaxy-13), P. fluorescens treated plants showed significantly improved leaf-water relations, glycinebetaine (10.78%) content, shoot potassium (23.07%), root calcium (50%) uptake, and yield parameters, respectively. Plant root length (71.72%) and potassium content (113.39%), root and shoot fresh and dry biomass, turgor potential (231.02%) and free proline (317.2%) content were maximum upon PGPR inoculation in consortium. Overall, Aas-11 (salt tolerant variety) showed significantly better performance than Galaxy-13 (salt sensitive variety). This study recommends B. pumilus and E. aurantiacum for the salt tolerant (Aas-11) and P. fluorescens for the salt sensitive (Galaxy-13) varieties, as potential bioinoculants to augment their growth and yield through modulation of morpho-physiological and biochemical attributes under saline conditions.